2001
DOI: 10.1002/dev.10014
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term retention of spatial navigation by preweanling rats

Abstract: The present study was designed to examine retention of spatial information in the immature, Fischer-344N rat using a savings paradigm. Following training to locate a hidden platform using extramaze cues, preweanling animals (17 days of age) were immediately probed by testing in the tank with the platform removed. One week later, pups (26 days of age) were given an additional four training trials immediately followed by a second probe test to examine the animals' memory for the location of the platform. Animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…The point in development at which the ability to place navigate emerges has been a matter of debate in previous literature, with estimates ranging from 17 to 21 days of age (Brown & Kraemer, 1997;Brown & Whishaw, 2000;Carman et al, 2002;Carman & Mactutus, 2001;Kraemer & Randall, 1995;Rudy & Paylor, 1988;Rudy et al, 1987;Tonkiss et al, 1993). Because nearly all these studies utilized protocols consisting of multiple, consecutive days of training, however, it is difficult to determine the precise day in development at which place navigation was first observed, particularly because the critical probe trial that assesses spatial learning is typically not administered until after the completion of training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The point in development at which the ability to place navigate emerges has been a matter of debate in previous literature, with estimates ranging from 17 to 21 days of age (Brown & Kraemer, 1997;Brown & Whishaw, 2000;Carman et al, 2002;Carman & Mactutus, 2001;Kraemer & Randall, 1995;Rudy & Paylor, 1988;Rudy et al, 1987;Tonkiss et al, 1993). Because nearly all these studies utilized protocols consisting of multiple, consecutive days of training, however, it is difficult to determine the precise day in development at which place navigation was first observed, particularly because the critical probe trial that assesses spatial learning is typically not administered until after the completion of training.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers (e.g. Carman et al, 2002;Carman & Mactutus, 2001) tend to identify the day in development at which spatial navigation emerges in terms of rats' ages at the onset of training, a more conservative approach is to restrict judgment of the initial emergence of spatial learning to the final day of training and/or the day a probe trial is given. Moreover, an even less ambiguous approach for identifying the precise day in development at which place learning emerges is to administer all training and test trials within a single day, as was done in the present study as well as one previous study (Brown & Whishaw, 2000), although this approach may entail certain disadvantages such as fatigue, hypothermia, or a retardation in acquisition rate that occurs with massed compared to spaced training (Commins, Cunningham, Harvey, & Walsh, 2003;Kraemer & Randall, 1995; but see Spreng, Rossier, & Schenk, 2002 for exception).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact may have favored learning in the younger group, as can be seen in the last two trials. Spatial learning at this age has been reported employing a procedure adapted to the pups requirements, such as a reduced size of the pool (Carman & Mactutus, 2001;Carman et al, 2002). However, using the present behavioral procedure the differences in latencies to locate the platform between both age groups were evident.…”
Section: Discussionmentioning
confidence: 67%
“…A spaced learning procedure was applied for minimizing fatigue, as proposed by Kraemer and Randall (1995). However, as it has been shown that reducing the task requirements may allow spatial learning in preweanlings (Carman & Mactutus, 2001;Carman, Booze, & Mactutus, 2002), a large circular pool was used in order to increase the difficulty of the task. Each subject received 10 blocks of training, applied in two daily sessions, morning and afternoon, during 5 consecutive days.…”
Section: Methodsmentioning
confidence: 99%